2017
DOI: 10.1038/s41598-017-02141-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct evaluation of influence of electron damage on the subcell performance in triple-junction solar cells using photoluminescence decays

Abstract: Tandem solar cells are suited for space applications due to their high performance, but also have to be designed in such a way to minimize influence of degradation by the high energy particle flux in space. The analysis of the subcell performance is crucial to understand the device physics and achieve optimized designs of tandem solar cells. Here, the radiation-induced damage of inverted grown InGaP/GaAs/InGaAs triple-junction solar cells for various electron fluences are characterized using conventional curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, we require a thorough understanding of what the PL intensity represents by considering the cell structures. We have proposed advanced analysis of solar cell operation using electroluminescence and time‐resolved PL characteristics , and our preliminary results have indicated that the luminescence efficiency of the InGaP cell under AM0, 1 sun illumination is not as high as we have expected from the relatively good cell performance . The reason for this is under investigation, but might explain the similarity with the InGaAs cells.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, we require a thorough understanding of what the PL intensity represents by considering the cell structures. We have proposed advanced analysis of solar cell operation using electroluminescence and time‐resolved PL characteristics , and our preliminary results have indicated that the luminescence efficiency of the InGaP cell under AM0, 1 sun illumination is not as high as we have expected from the relatively good cell performance . The reason for this is under investigation, but might explain the similarity with the InGaAs cells.…”
Section: Discussionmentioning
confidence: 88%
“…The degradation of diffusion current could result from the radiation‐induced defects acting as recombination centers. According to the study by Tex et al, in both electron‐irradiated GaInP and GaAs sub‐cells nonradiative recombination losses were observed 36 . When comparing the EOL properties of top and middle cells in dark, a larger degradation of diffusion current of the middle cell was observed in comparison to that of the top cell.…”
Section: Resultsmentioning
confidence: 97%
“…According to the study by Tex et al, in both electron-irradiated GaInP and GaAs subcells nonradiative recombination losses were observed. 36 When comparing the EOL properties of top and middle cells in dark, a larger degradation of diffusion current of the middle cell was observed in comparison to that of the top cell. However, the excess current of the top cell increased over 10 À5 A/cm 2 where it can affect the P MAX degradation whereas that of the middle cell was under 10 À6 A/cm 2 .…”
Section: Excess Current In Component Cellsmentioning
confidence: 93%
“…Irradiation effects in TJ GaInP/GaInAs/Ge cells have been well studied at room temperature (RT) [9][10][11] or at low temperature [12,13]. In these studies, the Ge doping level is around 10 18 at.cm -3 .…”
Section: Introductionmentioning
confidence: 99%